The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1021/la001110m
|View full text |Cite
|
Sign up to set email alerts
|

UV- or Visible-Light-Induced Degradation of X3B on TiO2 Nanoparticles:  The Influence of Adsorption

Abstract: Photodegradation of a textile dye X3B using either UV (λ g 320 nm) or visible light (λ g 450 nm) over three catalysts of highly adsorptive TiO2 nanoparticles in water has been examined. All the adsorption isotherms demonstrated the Langmuir type behavior. The common observation was confirmed that for all the reactions induced by UV or visible light, the apparent initial rate of X3B loss in the aqueous phase increased with the initial equilibrated concentration of X3B. However, this correlation was changed when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
128
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(135 citation statements)
references
References 16 publications
4
128
1
2
Order By: Relevance
“…This mechanism requires that the contaminant adsorbs on the catalyst surface as a prerequisite for efficient oxidation (Serpone and Pelizzetti, 1989). Most researchers observe a Langmuir adsorption isotherm and describe the adsorption-desorption process and the reaction rate constant based on the associated Langmuir-Hinshelwood (L-H) model (Xu and Langford, 2001;Rao et al, 2003), which is expressed as:…”
Section: Photocatalytic Reactors and Reaction Kineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…This mechanism requires that the contaminant adsorbs on the catalyst surface as a prerequisite for efficient oxidation (Serpone and Pelizzetti, 1989). Most researchers observe a Langmuir adsorption isotherm and describe the adsorption-desorption process and the reaction rate constant based on the associated Langmuir-Hinshelwood (L-H) model (Xu and Langford, 2001;Rao et al, 2003), which is expressed as:…”
Section: Photocatalytic Reactors and Reaction Kineticsmentioning
confidence: 99%
“…In general, adsorption studies are done in the dark and sometimes the adsorption capacity cannot be transferred quantitatively into irradiated systems (Xu and Langford, 2001). Studies indicated that increased adsorption to the catalyst surface translates to increased reaction rates (Xu and Langford, 2001;Rudder et al, 2004).…”
Section: Photocatalytic Reactors and Reaction Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface area of powder materials is commonly assessed by specific surface area defined as total area to mass of the solid sample and principles of Brunnauer-Emmett-Teller theory [28] are used for its measurement. When the effect of specific surface area on the (sono)photocatalytic activity of TiO2 is investigated, Langmuir-Hinshelwood behaviour [29] is often reported for the rate of photocatalytic reactions [30] and, thus, linear dependence of mass of the adsorbent on the photocatalyst surface (page 30 in [16]) is expected. Effectively, larger specific surface area leads to higher photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have revealed that the organic dyes could be effectively degraded using the TiO 2 -based photocatalytic process; however, the degradation of a majority of organic dyes are only under UV irradiation except for some dyes, such as alizarin red, which can be degraded under visible light using the TiO 2 -based photocatalysts based on the dyesensitized process. 10,11 Among different dyes, methylene blue dye (MB) is difficult to be decomposed under visible light irradiation and is usually regarded as a model dye contaminant to evaluate the activity of a photocatalyst. 12,13 Up to now, there were only few reports of MB dye degradation under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%